Inhaled Gases for Neuroprotection of Neonates: A Review - Tolaymat, Youness; Doré, Sylvain; Griffin, Hudson W.; Shih, Susana; Edwards, Mary E.; Weiss, Michael D. (Frontiers in Pediatrics, 2020)
Importance: Hypoxic-ischemic encephalopathy (HIE) is a significant cause of morbidity and mortality in neonates. The incidence of HIE is 1–8 per 1,000 live births in developed countries. Whole-body hypothermia reduces the risk of disability or death, but 7 infants needed to be treated to prevent death or major neurodevelopmental disability. Inhalational gases may be promising synergistic agents due to their rapid onset and easy titratability. Objective: To review current data on different inhaled gases with neuroprotective properties that may serve as adjunct therapies to hypothermia. Evidence review: Literature review was performed using the PubMed database, google scholar, and ClinicalTrials.Gov. Results focused on articles published from January 1, 2005, through December 31, 2017. Articles published earlier than 2005 were included when appropriate for historical perspective. Our review emphasized preclinical and clinical studies relevant to the use of inhaled agents for neuroprotection. Findings: Based on the relevance to our topic, 111 articles were selected pertaining to the incidence of HIE, pathophysiology of HIE, therapeutic hypothermia, and emerging therapies for hypoxic-ischemic encephalopathy in preclinical and clinical settings. Supplemental tables summarizes highly relevant 49 publications that were included in this review. The selected publications emphasize the emergence of promising inhaled gases that may improve neurologic survival and alleviate neurodevelopmental disability when combined with therapeutic hypothermia in the future. Conclusions: Many inhaled agents have neuroprotective properties and could serve as an adjunct therapy to whole-body hypothermia. Inhaled agents are ideal due to their easy administration, titrability, and rapid onset and offset.